MSME Empowerment Strategies for Green Business Transformation and Sustainable Eco-Friendly Product Development - Rusmini Barinong; Asnimar Asnimar; Ramlah P Ramlah P (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
The empowerment of Micro, Small, and Medium Enterprises (MSMEs) is one of the key strategies for achieving sustainable economic growth and improving public welfare. This study aims to formulate an MSME empowerment strategy that integrates green business practices, the development of environmentally friendly products based on local resources, and national development policy priorities through a SWOT-AHP approach to produce a more comprehensive strategic model in support of sustainable MSME competitiveness. This study was conducted in Makassar City, Maros Regency, and Gowa Regency. Data obtained through observation, documentation, in-depth interviews, and focus group discussions (FGDs) were analyzed using a combined SWOT-AHP method. The results indicate that the following strategies can be implemented: Development of Innovative Green Products Based on Local Resources (SO1), Strengthening the Identity of Environmentally Friendly Local Products as a Key Competitive Advantage (ST1), Improving Digital Literacy and Branding of Environmentally Friendly Products (WO3), Training and Mentoring in Green Business Practices by NGOs and Universities (WO1), and Utilizing Government Support and E-commerce for the Promotion of Green Products (SO2). This study makes a conceptual contribution through the development of a strategic model for MSME empowerment that integrates green entrepreneurship, product development based on local resources, national policy priorities (Asta Cita), and the SWOT-AHP approach as a framework for strategic decision-making aimed at achieving sustainable competitiveness for MSMEs.